Effect of Post Processing Heat Treatment on the Cyclic High Temperature Hot Corrosion Behavior of the Laser Powder Bed Fusion Processed Inconel 718 - Sahu, Saroj Kumar; Dalai, Renu Prava; Shaik, Nagoor Basha; Yuangyai, Chumpol; Behera, Ajit (My University, 2026)
In the present investigation, the cyclic hot corrosion behavior of laser powder bed fusion (LPBF)-processed Inconel-718 superalloy subjected to single-aging (HT-1) and double-aging (HT-2) heat treatments was systematically evaluated. Tests conducted at 850°C for 96 h in a Na2SO4-NaCl-NaVO3 molten salt environment demonstrated that HT-2 exhibited significantly enhanced corrosion resistance. The cumulative weight gain for HT-2 was 4.8 mg/cm2, compared to 5.7 mg/cm2 for HT-1 (an approximate 15.8% reduction), alongside a notably lower calculated corrosion rate (584.0 vs. 693.5 mg/cm2/year). Cross-sectional analysis indicated that HT-2 formed a thinner, denser, and more adherent oxide scale—primarily Cr2O3 and NiCr2O4 spinel—with reduced chromium depletion beneath the oxide layer. This improved corrosion resistance of HT-2 is attributed to its refined precipitate distribution and enhanced chemical homogeneity, which promote uniform chromium diffusion and the formation of a stable protective oxide barrier. This stable oxide scale effectively limits oxygen ingress, molten salt penetration, and scale spallation during cyclic thermal exposure. Overall, optimized double-aging significantly enhances the cyclic hot corrosion resistance of LPBF-processed Inconel-718. These findings provide important insights into tailoring post-processing heat treatments to improve the high-temperature durability of additively manufactured superalloys.
Keywords: double aging; hot corrosion; Inconel-718 superalloy; laser powder bed fusion; oxide layer; single aging